1999
DOI: 10.1063/1.370770
|View full text |Cite
|
Sign up to set email alerts
|

Phonon damping in thin films of Fe

Abstract: The phonon density of states ͑DOS͒ in thin films of polycrystalline ␣-Fe was measured by inelastic nuclear resonant scattering of synchrotron radiation. The thin-film DOS exhibits significant deviations from the DOS of bulk Fe, which we attribute to phonon lifetime broadening in the confined geometry. The measured DOS can be described with a damped harmonic oscillator model for the phonons with different quality factors Qϭ25(2) and Qϭ13(1) for layer thicknesses of 28 and 13 nm, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 13 publications
(15 reference statements)
3
34
0
Order By: Relevance
“…(i) The decrease in intensity of high-energy modes (15 and 18 meV) was observed before in various nanoscale systems 12,13,16,19,[21][22][23][24][25] , an effect which was found to originate from phonon scattering. From the TEM study, it was concluded that a single Sn island is composed of many Sn crystallites.…”
Section: B Phonon Density Of Statesmentioning
confidence: 79%
See 1 more Smart Citation
“…(i) The decrease in intensity of high-energy modes (15 and 18 meV) was observed before in various nanoscale systems 12,13,16,19,[21][22][23][24][25] , an effect which was found to originate from phonon scattering. From the TEM study, it was concluded that a single Sn island is composed of many Sn crystallites.…”
Section: B Phonon Density Of Statesmentioning
confidence: 79%
“…The phonon density of states (PDOS) of low dimensional systems is expected to be modified due to the restriction of phonon propagation [7][8][9][10][11] . Previously, clear differences between the phonon density of states of bulk and that of nanostructures have been observed, with as most commonly observed anomalies in the phonon spectra of nanostructures: an enhancement of low-energy modes, appearance of high-energy modes above the cut-off energy of the bulk material and a broadening of the PDOS features [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . For thin films, the broadening of features in the PDOS was attributed to phonon damping 13,19,27,28 and the enhancement of low-energy phonon modes due to the appearance of surface modes 14,19,27 .…”
Section: Introductionmentioning
confidence: 99%
“…[62][63][64][65][66] Such a shift could reduce the probability of the largeangle phonon scattering events required to return L (T ) to the Sommerfeld value at high T, thereby requiring higher temperatures to finally reenter the WF regime. However, our calculations suggest that the shifts in phonon DOS required to explain the ∼ 20% reduction in L seen here are so large that they would drive deviations of the heat capacity away from bulk-like values, in contrast to experimental data showing very good agreement between bulk and even very thin Au and Cu films.…”
Section: -47mentioning
confidence: 99%
“…Another source of reduction in the phonon lifetime originates from a smaller grain size. The DHO model has been used to describe size effects in metal nanostructures 29,30 . Indeed, the lifetime in nanostructures is expected to decrease due to the smaller mean-free-path induced by the smaller crystallite size.…”
Section: B Nuclear Inelastic Scatteringmentioning
confidence: 99%